Response of groundwater and soil displacement at slope of electric transmission tower due to rainfall events - Hazwani N.K.; Fathoni U.; Rohayu C.O.; Arazad A.Z. (Science Publishing Corporation Inc, 2023)
Climate change is one of the global challenges that give high impact to the environment and societies nowadays. One of the impacts of climate change is slope failure due to fluctuations in rainfall pattern. This paper aims to investigate the response between groundwater, soil displacement to rainfall and rainfall duration. The study was conducted by site observation at three different locations located under a transmission tower at hilly topography area. All parameters are observed hourly by specified instruments installed in the studied slopes. The study found that rainfall does not cause changes to groundwater and cumulative soil displacement increased proportionally to the amount of rainfall. The analysis extended on determining the correlation between displacement to the amount of received rainfall and rainfall duration by the statistical approach and the predictive variability is 91%. The mathematical equation expressed by this study could be used in predicting soil displacement based on rainfall events, the possibility of landslide occurrence or future modelling purposes. 2018 Authors.